Natural Stone and Architectural Heritage - Pereira, Lola (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is made up of contributions dealing with heritage stones from different countries around the world. The stones are described, as well as their use in vernacular and contemporaneous architecture. Heritage stones are those stones that have special significance in human culture. Examples include some very important stones that have been either neglected because they are no longer extracted, or stones that have great significance in commercial terms but knowledge of their national and/or international heritage has not been well documented. In this collection of articles, we have tried to spread awareness of architectural heritage around the world, the natural stones that have been used in its construction, and the need to preserve historical quarries that once provided the source of such stones. Historical quarries are linked to regional culture and tradition. Because of the specific technical and aesthetical characteristics of heritage stones, which have lasted for centuries, these historical quarries should be preserved to be able to use the stones for the proper restoration of monuments and historical buildings to avoid negative actions that can be observed in many places in the restoration of buildings, which are some times part of World Heritage sites. The final intention of this book is to continuosly grow the interest on this fascinating subject of heritage stones.